Metabolomic Study of Obesity and Its Treatment with Palmitoylated Prolactin-Releasing Peptide Analog in Spontaneously Hypertensive and Normotensive Rats - Čermáková, Martina; Pelantová, Helena; Neprašová, Barbora; Šedivá, Blanka; Maletínská, Lenka; Kuneš, Jaroslav; Tomášová, Petra; Železná, Blanka; Kuzma, Marek (Journal of proteome research, 2019)
In this study, the combination of metabolomics and standard biochemical and biometric parameters was used to describe the metabolic effects of diet-induced obesity and its treatment with the novel antiobesity compound palm11-PrRP31 (palmitoylated prolactin-releasing peptide) in spontaneously hypertensive rats (SHR) and normotensive Wistar Kyoto rats (WKY). The results showed that SHR on a high-fat (HF) diet were normoglycemic with obesity and hypertension, while WKY on the HF diet were normotensive and obese with prediabetes. NMR-based metabolomics revealed mainly several microbial cometabolites altered by the HF diet, particularly in urine. The HF diet induced similar changes in both models. However, two groups of genotype-specific metabolites were defined: metabolites specific to the genotype at baseline (e.g., 1-methylnicotinamide, phenylacetylglycine, taurine, methylamine) and metabolites reacting specifically to the HF diet in individual genotypes (2-oxoglutarate, dimethylamine, N-butyrylglycine, p-cresyl sulfate). The palm11-PrRP31 lowered body weight and improved biochemical and biometric parameters in both strains, and it improved glucose tolerance in WKY rats on the HF diet. In urine, the therapy induced significant decrease of formate and 1-methylnicotinamide in SHR and alanine, allantoin, dimethylamine, and N-butyrylglycine in WKY. Altogether, our study confirms the effectiveness of palm11-PrRP31 for antiobesity treatment.
Keywords: Prolactin-Releasing Hormone; Rats; Obesity; metabolomika; Metabolomics; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; hypertension; metabolom; potkani inbrední SHR; antiobesity therapy; obesity; Diet, High-Fat; krysa rodu Rattus; dieta s vysokým obsahem tuků; Body Weight; Metabolome; hormon uvolňující prolaktin; Anti-Obesity Agents; zvířata; tělesná hmotnost; metabolomics; obezita; NMR; Rats, Inbred SHR; high-fat diet; látky proti obezitě; Animals